Income stratification and polarization in post-apartheid South Africa - Machema, Ratjomose Petrose (School of Economics, 2019)
The thesis explores the patterns and evolution of income polarization, income stratification, and social polarization in post-Apartheid South Africa. It uses data from a survey conducted at the end of Apartheid, and data from two post-Apartheid surveys to understand the socio-economic transformation the country has undergone since the end of Apartheid. At the dawn of democracy in 1994, South Africa implemented many reforms to redress the effects of Apartheid. Two decades after the fall of Apartheid, the country is still battling against the social and economic hierarchies bestowed during the period of Apartheid. Black/African people, for example, still constitute at least 90% of the poor, unemployment hovers around 25% (with Blacks/African having 32% unemployment rate), and inequality is unchanged. There are also concerns of increasing intolerance to diversity as well as plummeting levels of social cohesion in the country. Therefore, if these disparities are not properly understood and addressed, disintegration could emerge as the future threat. Thus, our goal in this thesis is to examine the impact of political transition, which was followed by the enactment of a number of reforms, on the appearance (or disappearance) of economic distances and differences across population groups. This investigation is carried out through the perspective of income polarization and income stratification literature. Chapter 2 presents the analysis of the concepts of bi-polarization and polarization on the distribution of income in South Africa between 1993 and 2014-2015. Applying the non-parametric relative distribution approach and the summary measures of bipolarization and polarization, the chapter finds that, from 1993 to 2008, as inequality rises, both notions of polarization also increase, but at a much higher rate such that the distribution becomes perfectly bi-polar. During the period between 2008 to 2014, the level of bi-polarization falls below its 1993 level. Given the axiomatised link between bi-polarization and the size of the middle class, the results point to an increase in the size of the middle class in South African since the fall of apartheid. Lastly, the chapter finds that the distribution of government transfers and that of remittances have a depolarizing effect, while the distribution of labour income and of capital income have a tendency to erect poles on the national income distribution. Chapter 3 attempts, on the basis of Analysis of Gini, to provide the extent to which the income distributions of racial groups are hierarchically ordered along the national income distribution. Hierarchically ordering of income distributions assumes convergence, or lack of it, of incomes and of education across the racial groups. Therefore, first the chapter presents the rate of convergence of education and of income across the racial groups to serve as a backdrop in the analysis of overlapping of distribution of income across the racial group. The chapter finds that the income distribution of Whites overlaps less with that of the overall population and that of other racial groups, and changes in the distribution of labour income, and of capital income are likely to increase the degree of income stratification (or reduce degree overlapping of income distributions). Chapter 4 tries to demonstrate how social gaps across racial groups have evolved in post-Apartheid South Africa. To operationalize a measure of social gaps, we use the degree to which one feels identified and thus defends the interest of his racial group. This is referred to as a degree of radicalism. Through a series of regressions, the chapter shows how the degree of radicalism decreases with household wealth, level of education, employment, and satisfaction with life. Using the distribution of radicalism to quantify alienation, the chapter shows a fall in the scores of social polarization, which is largely driven by a fall in between-group polarization. Given that within group polarization rises concurrently with a fall in between-group polarization, this implies a trade-off between internal heterogeneity and external homogeneity. In short, the thesis advances our understanding of the normatively undesirable issue of distances and differences across groups and highlights the often neglected, yet indispensable, dimensions of an income distribution.